Electrochemical oxidative radical cascade cyclization of olefinic amides and thiophenols towards the synthesis of sulfurated benzoxazines, oxazolines and iminoisobenzofurans. Issue 20 (5th October 2021) - Lu, Fangling; Xu, Jie; Li, Hao; Wang, Ke; Ouyang, Dandan; Sun, Linghong; Huang, Mingna; Jiang, Jianwei; Hu, Jianguo; Alhumade, Hesham; Lu, Lijun; Lei, Aiwen
Abstract : Heterocycles containing N and O are important structures in pharmaceuticals, agrochemicals and functional molecules. Abstract : Heterocycles containing N and O are important structures in pharmaceuticals, agrochemicals and functional molecules. The synthesis of these compounds usually requires complex substrates and harsh reaction conditions. Herein, we introduce a mild and efficient electrochemical oxidative strategy to construct benzoxazines, oxazolines and iminoisobenzofurans without the requirement of a transition-metal catalyst and an external oxidant. In a simple undivided cell, various olefinic amides and thiophenols/diselenides react to generate 69 examples of thiolation and selenylation heterocycles in up to 83% yields. Furthermore, this radical cascade reaction provided a facile method for constructing C–S/C–Se and C–O bonds in one step.